From Obtaining to Degradation of PHB: A Literature Review. Part II (2018)
In our previous review (Part I - Material Properties), the chemical, physical and morphological properties, applications and mechanisms of obtaining poly (3-hydroxybutyrate) were discussed. PHB is a biologically based polymer that presents itself as an ecological option due to its characteristic degradation before environmental factors and due to the action of microorganisms such as algae, fungi and bacteria. In this second review, aspects related to the types of degradation to which this polymer is subjected and the necessary conditions for its degradation are addressed. Among these mechanisms are thermo-degradation, thermo-mechanical degradation, abiotic degradation, photo degradation and biodegradation. It is understood that the degradation of PHB can be seen as an advantageous feature of this material. This review complements the previous one and uses the same terminology.